Exports and the exchange rate: A general equilibrium perspective - Patrick Alexander; Abeer Reza (Bank of Canada, 2022)
Understanding and predicting the evolution of exports after a change in the nominal exchange rate is of central importance in international economics. Most of the literature focuses on estimating this relationship by reduced form, with the aim of uncovering a single structural parameter, but theory suggests it could differ depending on the shock that drives the movement in the exchange rate. Building on this insight, we develop a small-open-economy SVAR model to derive structural shocks that affect the exchange rate. We then estimate this model using Canadian data and construct the response of exports relative to the response of the exchange rate, conditional on each shock. Our findings suggest that this relationship differs greatly from one shock to another, where domestic shocks generate a much weaker relationship than global shocks. We show that these differences can be reconciled with theoretical results from a small-open-economy New Keynesian model where Canadian exports are largely invoiced in US dollars. Finally, we highlight how our results help to inform recent discussions on the evolution of the exchange rate elasticity over time, the benefits of a flexible exchange rate, and the impact of terms of trade movements on exports.
Keywords: F31; F32; F33; F41; 330; Exchange rates; International topics; Trade integration; Exchange rate regimes; Balance ofpayments and components; Business fluctuations and cycles; Monetary policy transmission